A descriptive phenomenological study of the lived experience of the creative design process among students of graphic design - Mohd Hafnidzam Adzmi,; Zahari Ishak,; Che Aleha Ladin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The use of technologies such as Computer-Aided Design (CAD) is significant and has a profound effect on the Creative Design Process. The widely studied process in Creativity research such as Divergent Thinking (DT), Convergent Thinking (CT), and Analogical Thinking (AT) can describe the Creative Design during the process of producing and the implementation of ideas. The article employs the Descriptive Phenomenological method by collecting verbalized data from seven participants who are at the time of this study are enrolled in a Design Course, specifically Graphic Design. Three design projects are designed specifically to collect verbalized data through the think-aloud and stimulated recall method. Another data source that is used to support interpretation are screen recordings of the of the participants Creative Design process. The findings include seven themes that are associated with the experience of Creative Design and are used to describe the Creative Design Process with CAD through DT, CT, and AT and their relationship through the transformations of conceptual knowledge and technical skills. The article then discusses the role of Conceptual and Technical Knowledge that went through the process of selection and mapping in AT to induce DT and CT in ideation and its expansion through the process of learning. Finally, the article will present the limitations of this study and suggestions for future research.